Komunikasi Partisipatif Budidaya Kakao Sekolah Lapang untuk Pengendalian Hama dan Penyakit serta Penanganan Pascabanjir di Desa Sajau - Natalia Susanti, Agnes; Trisyanti, Novriani; Yehezkiel; Suwartika Kusumadiarti, Rini; Tisnawati, Rini; Kurniawati, Rina (PADMA, 2024)
This community service discusses participatory communication strategies applied in a field school for pest and disease control and post-flood management in cocoa cultivation in Sajau Village, Bulungan Regency. The main focus of the field school was the participatory approach used, the methods applied, and the results achieved. The research shows how active community involvement can influence sustainable farming practices, with an emphasis on improving the effectiveness of pest control, disease management and post-flood recovery.